1982
DOI: 10.1002/bjs.1800690313
|View full text |Cite
|
Sign up to set email alerts
|

The effect of surgical drainage materials on colonic healing

Abstract: The effect of surgical drainage materials on rat colonic healing has been investigated in a prospective randomized and controlled study. Latex, silicone rubber (Silastic), polyvinylchloride (PVC) and polytetrafluoroethylene (Teflon) tubes were implanted alongside a colonic anastomosis and compared with a 'no drain' group using mechanical and histological assessments. There was a significant increase in anastomotic leakage in the latex group in which there appears to be a local inhibition of healing. Silastic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
5

Year Published

1983
1983
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 5 publications
0
15
0
5
Order By: Relevance
“…Studies in animal models have shown that the use of drains near colonic anastomosis is associated with an increased incidence of anastomotic leakage, morbidity and mortality. 92 Randomised controlled trials have demonstrated no benefit for the use of routine drains for intraperitoneal colonic anastomoses, and their use has largely been abandoned. 93,94 Many surgeons continue to drain rectal anastomoses which lie below the peritoneal reflection within the pelvis, in which haematoma and fluid collections may accumulate.…”
Section: The Role Of Drains To Coloanal and Colorectal Anastomosesmentioning
confidence: 99%
“…Studies in animal models have shown that the use of drains near colonic anastomosis is associated with an increased incidence of anastomotic leakage, morbidity and mortality. 92 Randomised controlled trials have demonstrated no benefit for the use of routine drains for intraperitoneal colonic anastomoses, and their use has largely been abandoned. 93,94 Many surgeons continue to drain rectal anastomoses which lie below the peritoneal reflection within the pelvis, in which haematoma and fluid collections may accumulate.…”
Section: The Role Of Drains To Coloanal and Colorectal Anastomosesmentioning
confidence: 99%
“…An early study found anastomotic breakdown in nearly 50% and extensive adhesion formation in all dogs after placement of latex rubber Penrose drains [24]. A publication on rats reported an increased leakage rate after implantation of latex but not after silicone rubber, polyvinyl chloride, and polytetrafluoroeth-ylene tubes [25]. However, another study with a similar design resulted in decreased resistance of colonic anastomoses with latex drains [26].…”
Section: Discussionmentioning
confidence: 97%
“…There are surgeons who believe that drainage of peritoneal cavity is impossible, and therefore, prophylactic drainage is useless [15,16]. The surgeons who are opposed to drainage believe that it [17][18][19][20][21][22] (A) Actually stimulates the formation of serous fluid (B) Can lead to infection from outside (C) Increases the rate of leakage by preventing the mobilization of omentum and adjacent organs, obstructing their sealing action on suture line or even creating leakage by mechanical erosion of the anastomoses (D) Is walled off quickly Although there is a considerable theoretical and practical evidences in favor of drainage, the dispute about "to drain or not to drain" the peritoneal cavity after elective colorectal surgery remains open [23]. Anastomotic dehiscence is a serious complication leading to major mortality and morbidity of colorectal surgery [24].…”
Section: Drain Vs No Drainmentioning
confidence: 99%